Far East Scarlet-Like Fever: A Review of the Epidemiology, Symptomatology, and Role of Superantigenic Toxin: Yersinia pseudotuberculosis-Derived Mitogen A - Amphlett, A. (Open Forum Infect Dis, 2015)
Far East scarlet-like fever (FESLF) is a severe inflammatory disease that occurs sporadically and in outbreaks in Russia and Japan. Far East scarlet-like fever is caused by Yersinia pseudotubuclosis infection, an organism that typically causes self-limiting gastroenteritis in Europe. Studies suggest the ability of Far Eastern strains to produce superantigen toxin Y pseudotuberculosis-derived mitogen A is integral to FESLF pathogenesis. In Europe, human Y pseudotuberculosis infection typically occurs sporadically, in the form of a self-limiting gastroenteritis. In Russia and Japan, outbreaks of Y pseudotuberculosis infection cause severe systemic inflammatory symptoms. This disease variant is called FESLF. Geographical heterogeneity exists between virulence factors produced by European and Far Eastern Y pseudotuberculosis strains, implicating superantigen Y pseudotuberculosis-derived mitogen A (YPMa) in the pathogenesis of FESLF. This article describes the epidemiology and clinical features of FESLF, and it presents the evidence for the role of YPMa in FESLF pathogenesis.